The “Gender Agenda” in Agriculture for Development and Its (Lack of) Alignment With Feminist Scholarship - Farhall, Kate; Rickards, Lauren (Frontiers in Sustainable Food Systems, 2021)
Sustainable food systems require sustainable agriculture. To achieve this, we argue, inclusive approaches are required that incorporate the voices and lived experiences of diverse social groups. In agriculture-based international development efforts (known as Agriculture for Development or A4D), it is increasingly being recognised that sustainable agriculture requires attention to gendered power relations. In the past, gender inequality has been a major barrier to developing inclusive, sustainable food systems, and continues to be so today. At the same time, however, gender is increasingly ‘on the agenda’ in A4D. Yet what sort of agenda is being promoted and to what extent does it reflect progress in feminist scholarship? We examine the burgeoning ‘gender agenda’ through the lens of policy materials produced by prominent A4D organisations. In doing so, we find problematic narratives that instrumentalise women in the name of sustainable agricultural development. However, we also find other more transformative discourses that, in troubling the drivers of gender inequality and promoting shared responsibility for change, reflect a deeper awareness of feminist scholarship. In any effort to advance sustainable agriculture, further progress is needed to address the myriad ways gender pervades not just development settings but development institutions and donor nations, and contributes to the production of as well as responses to global A4D challenges.